(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to demonstrate the impact of the acceptable solvency of the National Insurance Company on the investment activity in it, as the research assumes the existence of a statistically significant relationship between the acceptable solvency variable and the investment variable, and the researcher took the National Insurance Company as a place to conduct the research, as it is the first insurance company Watania was established in the fifties of the last century, and it has a long history in the practice of investment activity, and the company’s financial statements for the period from (2010-2019) were relied on, and the annual reports issued by the company as well as records are tools for gathering information, and one of the most important conclusions was (low investment return What comes from investing the company’s money despite the large amounts directed towards investment, as the percentage of return to total revenues does not exceed 9%, which gives an indication of the inefficiency of the investment decisions taken by the company during the years of the research sample, and the company relied heavily on Insurance premiums in achieving revenues, which may expose them to the risks of financial insolvency in the event of a decrease in the income of the insurance activity), and one of the most prominent recommendations of the researcher (adopting the indicators approved in the research to assess the Financial solvency and investment activity in the National Insurance Company and the rest of the companies operating in the Iraqi insurance sector).